Changes in Active Travel Among Adolescents in Active School Flag Between 2022–2024 (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Whole-of-school programmes to promote physical activity (PA) seldom focus on travel to and from school, yet active travel (AT) is an opportunity for being physically active. In Ireland, the Active School Flag (ASF) is a multi-tiered (try it out, certificate – school activities, flag – community activities) programme with the aim of promoting PA opportunities in the school and community. The purpose of this study was to examine the school-level changes in AT across three academic years during the ASF programme.Methods: Second-level students in ASF schools were asked to complete an online survey every autumn for three years. Target recruitment rates were >50% of students throughout the school. Travel to and from school was asked independently and combined for analyses. PA was measured using self-report of behaviour in the last week. The year of survey was a predictor for a logistic regression model, where travel by car and 2022 were the reference categories after controlling for individual characteristics (gender and age) and physical activity. Odds ratio (OR) and 95% confidence interval (CI), for each school and as a pooled sample, determined statistically significant changes.Results: There were 21 schools involved in ASF in 2022, 2023, and 2024, with students (n = 30,143) who completed surveys. Half of all the students (50%) reported to AT, although the range among schools was between 25%–77%. No statistically significant changes over the three years for the pooled sample were found. However, statistically significant changes were found in 10 of the schools (5 increased AT in 2024 with range of OR = 1.4 (CI = 1.1–1.7) – 1.9 (CI = 1.2–3.0), 3 decreased AT in 2024 with range of OR = 0.5 (CI = 0.3–0.8) – 0.7 (CI = 0.5–0.9) since 2022) after adjusting for gender, age and physical activity level).Conclusion: AT was not changed in the majority of ASF schools, although there were increases in some and decreases in others. These results emphasise the potential for the ASF to encourage more AT as part of the school and community programme. The lessons from schools that have changed may be useful for future recommendations to increase AT